2020
DOI: 10.1016/j.actbio.2020.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Collagen hydrogel confinement of Amyloid-β (Aβ) accelerates aggregation and reduces cytotoxic effects

Abstract: Alzheimer's disease (AD) is the most common form of dementia and is associated with the accumulation of amyloid-β (A β), a peptide whose aggregation has been associated with neurotoxicity. Drugs targeting A β have shown great promise in 2D in vitro models and mouse models, yet preclinical and clinical trials for AD have been highly disappointing. We propose that current in vitro culture systems for discovering and developing AD drugs have significant limitations; specifically, that A β aggregation is vastly di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…This is consistent with the Aβ pretreatment process that was used to ensure a consistent population of Aβ monomers at the start of each experiment. 15 All conditions showed the presence of aggregated Aβ (ThT fluorescence) that increased over time according to one of four trends: (1) a pronounced lag phase and then rapid aggregation, (2) a two-phase increase in fluorescence depicting an overall relatively slow rate of aggregation, (3) a brief slow phase and then rapid aggregation, and (4) a two-phase increase in fluorescence suggesting an overall relatively fast rate of aggregation.…”
Section: Resultsmentioning
confidence: 95%
“…This is consistent with the Aβ pretreatment process that was used to ensure a consistent population of Aβ monomers at the start of each experiment. 15 All conditions showed the presence of aggregated Aβ (ThT fluorescence) that increased over time according to one of four trends: (1) a pronounced lag phase and then rapid aggregation, (2) a two-phase increase in fluorescence depicting an overall relatively slow rate of aggregation, (3) a brief slow phase and then rapid aggregation, and (4) a two-phase increase in fluorescence suggesting an overall relatively fast rate of aggregation.…”
Section: Resultsmentioning
confidence: 95%
“…This discovery might partially explain why the Aβ targeting drugs fail in clinical trials since the much higher physiological concentration of Aβ is used in vitro. Recently, Simpson et al (2020) identified differences of Aβ aggregation and cytotoxicity between 2D in vitro models (typically culture cells on flat plastic or glass substrates) and 3D environments, such as collagen hydrogels in tissue culture models. Combined with FCS, they found that the size of Aβ aggregates in 3D collagen hydrogel is 25-200 times larger in diameter than 2D culture, suggesting a vastly different aggregation process.…”
mentioning
confidence: 99%
“…Dynamics of hydrogel microstructures can be characterized by a) analysis of probe diffusion via fluorescence recovery after photobleaching (FRAP) and dynamic light scattering (DLS), b) estimation of mesh size from swelling data and Flory-Rehner-Huggins theory, and c) examination of mechanical properties by rheology and dielectric relaxation (Aggeli et al, 1997(Aggeli et al, , 2001; Barretta et al, 2000;Bohidar, 2001;Burne and Sellen, 1994;Canal and Peppas, 1989;Johnson et al, 1995;Pluen et al, 1999;Pusey and Van Megen, 1989;Simpson et al, 2020). Unfortunately, these techniques are most often incapable of distinguishing between features of the hydrogel and features of the protein because signatures related to the hydrogel typically overshadows the small signal generated by features of individual proteins.…”
Section: Confinementmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS) detects the individual photons of fluorescently-labeled molecules that pass through a very small confocal volume. Photon fluctuation data can be used to generate a correlation function, which can then be used to calculate molecular diffusion and size (Michelman-Ribeiro et al, 2007;Sengupta et al, 2003;Vagias et al, 2013;Vagias et al, 2017;Zustiak et al, 2010;Simpson et al, 2020). In cases where fluorophore photobleaching is a concern, raster image correlation spectroscopy (RICS) is similar to FCS but applies multiphoton excitation and rasterized scanning to limit fluorophore exposure to light (Fig.…”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation